Development of a strategic and tactical game plan for junior mining companies - Seeger, Michael Walter Fritz (My University, 2009)
ABSTRACT This thesis undertakes to present a game plan for junior mining companies. It culminates with a game plan model that incorporates all the key steps and tasks that mining investors and entrepreneurs need to use to establish globally competitive junior mining companies. It is based on the research of several listed junior mining companies. The game of junior mining is defined by rules, the player, the elements of playing, and the definitions of winning and scoring. The rules of the game are those defined by the resources industry and general business concepts. The mining assets around which the junior mining game is played are exploration projects, feasibility studies, mine development projects or operating mines. The player is the junior mining company intent on winning the game. Playing the game is done through executing the steps, tasks and simple models and matrices associated with the four business pillars: strategy development, legal and financial, operations management and risks management. The first pillar is strategic, while the last three pillars are tactical. For each business pillar, databases were developed, for the purposes of creating references and benchmarks for the game plan. The databases have been created from the analysis of twenty randomly selected junior mining companies, the author’s practical experiences and previous research. Scoring the game is undertaken by completing the game score matrix, which scores the mining assets, the business pillars and the financial performance, and provides an overall company score. The total company score highlights the strengths and weaknesses of the company. Undertaking the process of playing the game iteratively will lead to creating a globally competitive junior mining company. Winning the game is defined as creating a sustainable junior mining company, that grows to a mid-tier company, or is bought out by a major mining company. ii In the thesis, the game is played using the hypothetical case study of a of a coal junior mining company, with a marginal coal mine, an attractive feasibility study and an exploration project. Step by step the game is played leading to a company score and exposing the company’s strengths and weaknesses. The research concludes by presenting a holistic game plan model that can be applied to any junior mining company in any commodity in constantly changing resources industry dynamics.
Keywords: business plan; mining companies